Outcomes of microvascular flap reconstruction of the head and neck in patients receiving systemic immunosuppressive therapy for organ transplantation. Issue 7 (3rd May 2018) - Schaverien, Mark V.; Dean, Riley A.; Myers, Jeffrey N.; Fang, Lin; Largo, Rene D.; Yu, Peirong
Abstract : Background: For organ transplant recipients, cancer secondary to immunosuppressive therapy threatens long‐term survival. The associated multiple comorbidities make major free flap reconstruction following cancer surgery a complicated event. This study evaluates the outcomes of free flap reconstruction in this population. Methods: A retrospective chart review of all head and neck free flap cases in patients with a history of organ transplantation receiving systemic immunosuppressive therapy between 2005 and 2017 at a single‐institution was conducted. Results: Of 57 organ transplant patients, 25 patients (28 flaps) were included. Flaps used included the anterolateral thigh ( n  = 17), radial forearm ( n  = 4), latissimus dorsi ( n  = 3), fibula ( n  = 2), lateral arm ( n  = 1), and thoracodorsal artery perforator ( n  = 1) flaps. The most common organ transplant was kidney, then lung, liver, and heart. Mean inpatient stay was 8.2 days (range, 4‐28). Complications occurred in 15 patients, with no total or partial flap losses. Conclusion: Major head and neck free flap reconstructive surgery can be performed safely in organ transplant patients receiving immunosuppressive therapy. Meticulous multidisciplinary care is required to achieve consistently successful outcomes.